2006
DOI: 10.2478/v10053-008-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of perception and action in music performance

Abstract: INTRODUCTIONWhen performing musical sequences, people plan actions to produce acoustic events that communicate thoughts and emotions (for reviews see Gabrielsson, 1999;Jones & Holleran, 1992;Juslin & Sloboda, 2001;Palmer, 1997;Sloboda, 1982;1985;.Sequence production in contexts such as music and speech involves communicating a message through sound, a process that is probably guided by monitoring the perceived consequences of one's actions (Levelt, 1989;MacKay, 1987;Palmer & Drake, 1997). However, little resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 79 publications
4
65
1
1
Order By: Relevance
“…Thus, alternate feedback was not "disruptive" of performance, as other alterations of feedback pitch are (cf. Pfordresher, 2006). Further analysis suggested that the error rates shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, alternate feedback was not "disruptive" of performance, as other alterations of feedback pitch are (cf. Pfordresher, 2006). Further analysis suggested that the error rates shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…We here focus on the production of musical sequences on a piano keyboard and the associated role of auditory feedback. Many studies have shown that alterations of auditory feedback (AAF), such as delaying feedback onsets or altering feedback contents (pitch in music production), can disrupt sequence production (for reviews, see Pfordresher, 2006;Yates, 1963). One interpretation of such results is that AAF interferes with action planning, because perception and action may share an underlying cognitive representation for sequence structure (Pfordresher, 2006;cf.…”
mentioning
confidence: 99%
“…Finally, we refer to a review of studies demonstrating the role of auditory feedback in music performance by Pfordresher (2006). This study is of particular interest because it discussed the underlying principles of how auditory feedback influences many characteristics of a music performance.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the anchoring process mentioned earlier is most effective at promoting global stability when structural congruence is high. More generally, perception and action may be more tightly coupled-allowing more stable global coordination-when movement patterns and the 'melodic' contours of auditory goals are represented by a common set of transitional relations than when representations of two distinctive sets of transitional relations are simultaneously active (for related discussions, see Hoffmann, Stöcker, & Kunde, 2004;Hommel, Müsseler, Aschersleben, & Prinz, 2001;Klapp, Porter-Graham, & Hoifjeld, 1991;Koch, Keller, & Prinz, 2004;Pfordresher, 2006). It may be the case that the concurrent simulation of movements and auditory goals by internal models (see Wolpert & Ghahramani, 2000) runs more smoothly when they have a common transitional structure.…”
Section: Structural Congruencementioning
confidence: 99%